Evaluasi Program Bantuan Sosial Lansia Non Potensial di Kota Madiun dengan Model Context Input Process Product (CIPP) - Lisnavernita, Melasisca Yunanda; Akadira, Tora; Nurliawati, Nita; Vivaldi, Antonio (Jayapangus Press, 2024)
The non-potential elderly social assistance program is Madiun City's flagship program for handling helpless elderly which is implemented on an ongoing basis, but has never been evaluated for its effectiveness. The aim of the research is to describe the results of the match between program achievements and the initial design and to determine the driving and inhibiting factors of the program. The research method is descriptive qualitative, with data collection techniques using observation, interviews and documentation. Evaluation uses the Context, Input, Process, and Product (CIPP) model. The results of the Context evaluation explain that the program objectives and target priorities are in line with community needs. Input shows that the instruments for implementing the program are incomplete. Process describes program implementation as less effective. The product shows that the program objectives have been achieved but have not been maximized. Meanwhile, factors driving the success of the program include the commitment of the Mayor of Madiun, fairly complete regulations, funding support, and community participation in implementing the program. Inhibiting factors include the limited number of implementing human resources, the lack of synergy between various parties, and the lack of an integrated system. The conclusion is that this program is still needed for the treatment of non-potential elderly, but program improvements need to be implemented immediately so that the goals are achieved more optimally.